Innovation as a practice: Why automation will not kill innovation - Redín, Dulce M.; Cabaleiro-Cerviño, Goretti; Rodriguez-Carreño, Ignacio; Scalzo, German (Frontiers in Psychology, 2023)
As a result of contemporary culture’s focus on continuous innovation and “change before you have to,” innovation has been identified with economic gains rather than with creating added value for society. At the same time, given current trends related to the automation of business models, workers seem all but destined to be replaced by machines in the labor market. In this context, we attempt to explore whether robots and Artificial Intelligence (AI) will be able to innovate, and the extent to which said activity is exclusively inherent to human nature. Following the need for a more anthropological view of innovation, we make use of MacIntyrean categories to present innovation as a domain-relative practice with creativity and practical wisdom as its corresponding virtues. We explain why innovation can only be understood within a tradition as it implies participating in inquiry about the principle and end of practical life. We conclude that machines and “intelligent” devices do not have the capacity to innovate and they never will. They may replicate the human capacity for creativity, but they squarely lack the necessary conditions to be a locus of virtue or engage with a tradition.